THE RELATIONSHIP OF GENERATION Z WITH RELIGION - Vukojevic, Bojana (Politeia, 2021)
In recent years, there has been an increased interest in research into religiosity of different generations, especially Millenials. In this paper, we will examine the relationship of Generation Z to religion. As the most numerous population, characterised by insecurity and concern for the socio-economic and security aspects of the world in which we live, by digital mediation and socialisation accompanied by the availability of the Internet, by racial and ethnic diversity, and by supporting individual freedom and sexual amorphousness, they are the first post-Christian generation as well, shaping the world like no other generation to this day. Given the aforementioned, the subject of our research is the religious and spiritual values that this generation cultivates. The paper uses secondary data derived from the Pew Research Center research, as well as studies based on qualitative and quantitative research comparing different generation cohorts. The paper consists of three parts, with the first part presenting the sociological characteristics of Generation Z, the second one explaining the popular concepts of modern religiosity together with the respective pieces of criticism, and the final one observing Generation Z as representatives of the post-Christian world. Considering the overall social transformation that accompanies this generation, in conclusion we find that Generation Z treats religion and elements of religion as trends, that there is a search for ‘religious shortcuts’, i.e. that it channels its spirituality through rituals and ceremonies that meet their current needs and are not necessarily related to one religion.
Keywords: generation Z; religion; post-Christian world; popular culture